Association between colorectal cancer and arthritis among Americans in 2005–2016 - Zhongbo Hou; Niping Qin; Yanlin He; Jiang Chen; Yibo Cao; Wei Xie; Tianbao Xiao (BMC Cancer, 2025)
Abstract Background Colorectal cancer (CRC) ranks among the most prevalent cancers globally. Some studies have found that arthritis could reduce the risk of CRC through inflammatory immune mediation. However, there have been no reports on whether arthritis is related to CRC. Therefore, the correlation between arthritis and CRC was investigated to provide some theoretical support for understanding the prevention and diagnosis of CRC. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) to investigate the relationship between arthritis and CRC among Americans. A total of 300,106 adults participated in the study, and through a questionnaire survey, they were categorized into the control group and the CRC group. In this study, arthritis was considered the exposure variable, and 17 covariates were included. The relationship between the variables and CRC was then revealed through baseline characteristic analysis, association analysis, and stratified analysis. The predictive efficiency of arthritis for the CRC was assessed using the receiver operating characteristic curve (ROC) analysis. Finally, nomogram was created to evaluate the predictive capacity. Results A total of 297,681 control subjects and 2,425 CRC subjects within this survey. Significant disparities were observed between the two groups for all variables except for drink and poverty income ratio (PIR). Three models demonstrated a clear association between arthritis and CRC (model 1: odds ratio (OR) = 3.57, 95% confidence interval (CI) = 2.5–5.1, P = 0.00000000025; model 2: OR = 1.71, 95% CI = 1.15–2.53, P = 0.008; model 3: OR = 1.56, 95% CI = 1.03–2.38, P = 0.0369), indicating that the effect of arthritis on CRC was not significantly confounded by other covariates across the three models. Stratified analysis showed that arthritis was positively associated with CRC, and the area under the curve (AUC) was 0.818, indicating that arthritis was more effective in the prognosis of CRC. Finally, the decision curve and calibration curve indicated that the nomogram could effectively predict CRC. Conclusion This study found that arthritis had a strong association with the occurrence of CRC, providing ideas and strategies for its early detection.